PENINGKATAN PROFESIONALISME GURU DI SMK NEGERI CIKALONG KABUPATEN TASIKMALAYA, TAHUN PELAJARAN 2018/2019 - MAMAT RAHMAT (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Professional teachers must be able to implement four teacher competencies, namely: (1) pedagogic competence; (2) professional competence; (3) personality competence; and (4) social competence. Based on the results of observations made by researchers at SMK Negeri Cikalong, Tasikmalaya Regency, teacher professionalism still needs to be improved. The formulation of the research problem is as follows: 1) How are the efforts made in increasing the professionalism of teachers in Cikalong State Vocational School, Tasikmalaya Regency, 2) What are the indicators of teacher professionalism improvement in Cikalong State Vocational School, Tasikmalaya Regency, 3) What are the challenges faced in increasing the professionalism of teachers in Cikalong State Vocational School, Tasikmalaya Regency. This research method uses qualitative methods. Data collection tools and techniques are literature study, observation, interviews. The conclusions from the research are: 1) Efforts made to improve teacher professionalism at SMK Negeri Cikalong, Tasikmalaya Regency are: teacher development training or training, developing teacher duties and functions, conducting comparative study programs to other schools that have progressed, 2) Indicators of increasing professionalism teachers at SMK Negeri Cikalong Tasikmalaya Regency are as follows; teachers are more creative and innovative in carrying out their duties as teachers, mastering the curriculum, mastering subject matter, mastering learning methods and evaluations, loyal to assignments, disciplined. 3) The challenges faced in increasing professionalism at SMK Negeri Cikalong, Tasikmalaya Regency are as follows; there are still many teachers who have not mastered ICT, still low interest and motivation to participate in scientific forums, consumptive teacher lifestyle, low awareness of teachers about their duties and functions, internet access is still relatively difficult in the school environment, there is still little interest for teachers to continue education to a higher level or master's degree, teachers are less creative and innovative, there are still teachers who lack discipline, there is a delay in school BOPD, curriculum implementation is often not in accordance with what has been mutually agreed upon.